(3Gdbhd GdeYhd ajef gh HeSLO GdeOjfI GdQGJH GdChds - (3eMeO Hf QShd GdMSjfj, CHh YHO Gddg GdHQRNjs
(3ChdgG (B:s
(3hHYO abO hbY ai YGe Cda hSHYI hKeGfjf s
(3BNQgG (B:s
(3hHYV GYGOI ddcdGe GdChd adG MGLI Edi GdJYQV dQOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(474 (3c(B) s
Keywords: (3CUhd Gdabgs